Green Product Dan Environment Knowledge Sebagai Faktor Purchase Intention The Body Shop Kota Bandung - Vida Oriana, Aurel; Gaffar, Vanessa; Miftahuddin, Asep (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study aims to examine the influence of green products and environmental knowledge on consumer purchase intention toward The Body Shop products in Bandung, particularly to address the issue of the gap between positive perceptions of the brand’s sustainability commitment and actual consumer purchasing decisions of green products. The research method used a quantitative approach through surveys as the data collection instrument. A sample of 400 respondents was selected randomly from followers of the Instagram account @thebodyshopindo using Slovin's formula. The validity and reliability of the instruments were tested using the Rasch Model, while data analysis was conducted using Structural Equation Modeling (SEM). The results show that green products have a positive effect on consumer purchase intention. In addition, environmental knowledge also has a positive influence, both directly on purchase intention and as a mediating variable. The implication of this study is that companies need to intensify educational efforts aimed at consumers regarding sustainability issues and the benefits of using environmentally friendly products. Theoretically, this research contributes to the literature on consumer behavior, especially in the field of green marketing, and provides practical recommendations for companies in designing more effective and sustainable marketing strategies.